Hyperelastic constitutive analysis of silicone sheet as skin substitute / Siti Noor Azizzati Mohd Noor - Mohd Noor, Siti Noor Azizzati (2015)
Silicone Rubber is a potential skin substitute material, whereby its mechanical behaviour is also difficult to characterize. This study pioneers in its attempt to investigate the mechanical properties of Silicone Rubber materials via the integration of experimental, numerical and analytical approaches adapting hyperelastic constitutive equations. Initially, uniaxial tensile test is performed to measure the stress-stretch response of two types of Silicone Rubber based materials (i.e. Normal Grade and Food Grade) employing two testing standards (i.e. ASTM D2209 and ASTM D412). Three hyperelastic constitutive models (i.e. neo-Hookean, MooneyRivlin and Ogden) have been adopted to represent the materials behaviour and properties in terms of material constants for each Silicone Rubber which have been determined via numerical and analytical approaches. Engineering stress-stretch «()E A,) curve plot from numerical and analytical approach has been fitted to the experimental data. Results indicate that numerical approach provides better results than analytical approach in fitting the experimental data whereby the Mooney-Rivlin model gives the most accurate results to the experimental data compared to neoHookean and Ogden models. Therefore it can be concluded that numerical approach using the Mooney-Rivlin model is the closely hyperelastic constitutive model in representing the mechanical properties of Silicone Rubber materials